2014
DOI: 10.1002/ajmg.a.36524
|View full text |Cite
|
Sign up to set email alerts
|

Xq28 duplication overlapping the int22h‐1/int22h‐2 region and including RAB39B and CLIC2 in a family with intellectual and developmental disability

Abstract: Duplications involving terminal Xq28 are a known cause of intellectual disability (ID) in males and in females with unfavorable X-inactivation patterns. Within Xq28, functional disomy of MECP2 causes a severe ID syndrome, however the dosage sensitivity of other Xq28 duplicated genes is less certain. Duplications involving the int22h-1/int22h-2 LCR-flanked region in distal Xq28 have recently been linked to a novel ID-associated phenotype. While evidence for the dosage sensitivity of this region is emerging, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 19 publications
0
46
0
Order By: Relevance
“…Dysfunction of RyRs in neuronal cells leads to neurological disorders (Witham, Takano, Schwartz, & Alexov, ). A mutation in CLIC2 (H101Q) stimulates the activity of RyR channels and is associated with X‐linked intellectual disability (ID) in males, atrial fibrillation, cardiomegaly, congestive heart failure (CHF), seizures, and cognitive impairment (Andersen, Baldwin, Ellingwood, Smith, & Lamb, ; Chen et al., ; Witham et al., ). The residue H101 is present in the joint loop structure of CLIC2 (Cromer et al., ).…”
Section: Physiological Roles Of Clicsmentioning
confidence: 99%
“…Dysfunction of RyRs in neuronal cells leads to neurological disorders (Witham, Takano, Schwartz, & Alexov, ). A mutation in CLIC2 (H101Q) stimulates the activity of RyR channels and is associated with X‐linked intellectual disability (ID) in males, atrial fibrillation, cardiomegaly, congestive heart failure (CHF), seizures, and cognitive impairment (Andersen, Baldwin, Ellingwood, Smith, & Lamb, ; Chen et al., ; Witham et al., ). The residue H101 is present in the joint loop structure of CLIC2 (Cromer et al., ).…”
Section: Physiological Roles Of Clicsmentioning
confidence: 99%
“…This is partly because the CLIC2 gene is absent in the murine genome; therefore, knockout mice cannot be used to gain insights into its function. Human CLIC2 gene is present in the telomeric region of chromosome Xq28, and the duplication or lack of this gene were reported to cause mental retardation, developmental disability or epilepsy mainly in male children [13][14][15] CLIC2 gene mutations also caused cardiomegaly, in part because of its stimulating action on the ryanodine receptor while amplifying intracellular Ca 2+ signals 16 Recently, our pathologic investigation of surgically dissected tissue samples from cancer patients demonstrated that CLIC2 was expressed predominantly in non-cancer tissues rather than in cancer tissues. In this study, we investigated the localization of CLIC2 in cancer and surrounding non-cancer tissues from cases bearing hepatocellular carcinoma (HCC), metastatic colon cancer in the liver (Meta) and colorectal cancer (Colon) to gain insights into the functions of CLIC2 in normal and cancer cells and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…This observation emphasizes the importance of early recognition of the syndrome and timely examination of the shoulder musculature. Other neurological symptoms which may occur in Xq28 duplications as impaired intellectual development or hypotonia were not present in the affected family members [22].…”
Section: Discussionmentioning
confidence: 84%